Risk factors of late lesion growth after acute ischemic stroke treatment - Konduri, Praneeta; Bucker, Amber; Boers, Anna; Dutra, Bruna; Samuels, Noor; Treurniet, Kilian; Berkhemer, Olvert; Yoo, Albert; van Zwam, Wim; van Oostenbrugge, Robert; van der Lugt, Aad; Dippel, Diederik; et al. (Frontiers in Neurology, 2022)
Background: Even days after treatment of acute ischemic stroke due to a large vessel occlusion, the infarct lesion continues to grow. This late, subacute growth is associated with unfavourable functional outcome. In this study, we aim to identify patient characteristics that are risk factors of late, subacute lesion growth. Methods: Patients from the MR CLEAN trial cohort with good quality 24 hour and 1-week follow up Non-Contrast CT scans were included. Late Lesion growth was defined as the difference between the ischemic lesion volume assessed after 1-week and 24-hours. To identify risk factors, patient characteristics associated with lesion growth (categorised in quartiles) in univariable ordinal analysis (p<0.1) were included in a multivariable ordinal regression model. Results: In the 226 patients that were included, the median lesion growth was 22 (IQR 10-45) ml. In the multivariable model, lower collateral capacity (aOR:0.62(95% CI: 0.44-0.87); p=0.01), longer time to treatment (aOR: 1.04 (1-1.08), p=0.04), unsuccessful recanalization (aOR:0.57 (95% CI: 0.34-0.97); p=0.04), and larger midline shift (aOR: 1.18 (95% CI:1.02-1.36); p=0.02) were associated with late lesion growth. Conclusion: Late, subacute, lesion growth occurring between 1 day and 1 week after ischemic stroke treatment is influenced by lower collateral capacity, longer time to treatment, unsuccessful recanalization, and larger midline shift. Notably, these risk factors are similar to the risk factors of acute lesion growth, suggesting that understanding and minimizing the effects of the predictors for late lesion growth could be beneficial to mitigate the effects of ischemia.